Sağlık Çalışanlarında Problem Çözme Becerileri ile Karar Verme Stilleri Arasındaki İlişkinin İncelenmesi. - Akman Dömbekci, Hilal (Electronic Turkish Studies)
Decision-making can be briefly described as choosing among alternatives. There are five styles of decision-making: rational, intuitive, dependent, avoidant, and spontaneous. A problem is any situation that prevents reaching a goal. To cope with a problem, it is necessary to first understand it, identify alternative solutions, and predict the consequences of these alternatives. Deciding on the most beneficial alternative and achieving a solution represents success in problem solving. Each stage of the services provided in healthcare institutions may require critical decisions. Furthermore, healthcare services are institutions that differ from other services in that they are often faced with uncertain problems. It is desirable for employees in these institutions, which are involved in human health, to have high problem-solving skills. The purpose of this research is to examine the relationship between the problem-solving skills and decision-making styles of healthcare professionals. This research is quantitative, descriptive, and correlational in nature. The participants of the study were healthcare professionals working at a university hospital. 270 participants participated in the study. Data were collected using a demographic information form, a problem-solving skills scale, and a decision-making styles scale. SPSS was used for data analysis. Frequency analysis, t-test, ANOVA, and correlation analysis were conducted. The study determined that healthcare professionals' problem-solving skills were moderate and that they adopted a more rational decision-making style. Furthermore, as healthcare professionals' problem-solving skills increased, they were found to decrease their tendency to make decisions by avoiding them. Furthermore, as healthcare professionals' problem-solving skills increased, their spontaneous/impulsive decisions decreased.